2001
DOI: 10.1016/s0960-9822(01)00047-1
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Rho GTPases and PI 3-kinases during apoptotic cell phagocytosis by macrophages

Abstract: In vivo, apoptotic cells are removed by surrounding phagocytes, a process thought to be essential for tissue remodeling and the resolution of inflammation [1]. Although apoptotic cells are known to be efficiently phagocytosed by macrophages, the mechanisms whereby their interaction with the phagocytes triggers their engulfment have not been described in mammals. Here, we report that primary murine bone marrow-derived macrophages (using alpha(v)beta(3) integrin for apoptotic cell uptake) extend lamellipodia to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
132
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 29 publications
11
132
0
Order By: Relevance
“…Therefore, in the absence of WASp, other related molecules such as SCARs/WAVEs presumably contribute to the recruitment of the Arp2/3 complex and subsequent actin polymerization, as suggested for CR3-mediated phagocytosis (13). Consistent with this, we have observed that Rac, which can activate SCARs/WAVEs, as well as Cdc42, is required for apoptotic cell uptake (18,24).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, in the absence of WASp, other related molecules such as SCARs/WAVEs presumably contribute to the recruitment of the Arp2/3 complex and subsequent actin polymerization, as suggested for CR3-mediated phagocytosis (13). Consistent with this, we have observed that Rac, which can activate SCARs/WAVEs, as well as Cdc42, is required for apoptotic cell uptake (18,24).…”
Section: Resultssupporting
confidence: 84%
“…Cdc42 is known to activate WASp, and indeed we have observed that Cdc42 is required for uptake of apoptotic cells (18). It is likely that interaction between WASp and the Arp2/3 complex contributes significantly to the actin polymerization necessary for this process to occur (19).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…These data suggest that lamellipodial actin spreading is required for the formation of CD48iGFP APC extensions. Cdc42 regulates lamellipodial actin spreading (37) as well as phagocytosis (38) and macropinocytosis (44). When we blocked lamellipodial actin spreading with 100 nM dominant-negative Cdc42 as a protein transduction reagent (Cdc42dn) (37), only 31% of the T cell/APC couples showed CD48iGFP APC extensions as opposed to 69% with buffer only ( p Ͻ 0.001).…”
Section: Characterization Of the T Cell Invagination As Lamellipodialmentioning
confidence: 99%
“…In addition, apoptotic cell uptake is significantly regulated by the balance between Rac-1, which is required, and RhoA, which is inhibitory (30)(31)(32), and this balance can be seen both in vivo and in vitro, and across different cell types. This raises the intriguing possibility that an intrinsic, or induced, imbalance between these low-molecular-weight GTPases in potential efferocytes may contribute to the impaired clearance, and indeed to the potential for some smokers to develop COPD.…”
Section: Apoptotic Cell Clearance In Copdmentioning
confidence: 99%